Tentația livrescului și aventura formării intelectuale în jurnalele lui Leo Butnaru - Inga SOROCEAN (Philologia)
The article aims to research two of the personal diaries of the Bessarabian writer Leo Butnaru – Student during the Rhinoceros, published in 2000, and Theperimeter of the cage, edited in 2005, both considered diaries of self-formation and reading diaries. Starting from the premise that reading for pleasure is a self-building experience, but also one of self-discovery, I insisted on some key moments through which the diarist ensures the book-learning dimension of the diaries, transforming daily events into an adventure of intellectual formation. Our attention was focused on the diaristic character, the young journalism student Leo Butnaru, this homo legens, for whom reading becomes a modus vivendi, an essential act for shaping the self, facilitating the initiation of the self into world literature and the connection to the European aesthetic space.